ENTREPRENEURIAL ATTITUDE AND STUDENTS BUSINESS START-UP INTENTION: A PARTIAL LEAST SQUARE MODELING - Widayat, Widayat; Ni matuzahroh, Ni matuzahroh (Jurnal Manajemen dan Kewirausahaan, 2017)
This article is designed to examine the role of the entrepreneurial spirit, education and in building an attitude about working as an entrepreneur, and his influence on the intention to start a business, to the students. Data were collected using a questionnaire has been prepared and maintained the validity and reliability. Questionnaires given to the respondent students were selected as samples at several universities in Malang, East Java, Indonesia. The collected data were analyzed by using Partial Least Square. The analysis showed entrepreneurial spirit and education contribute to the formation of entrepreneurial attitudes. Attitudes are formed encourage entrepreneurship intentions to start a business significantly.